2016
DOI: 10.1097/qai.0000000000001046
|View full text |Cite
|
Sign up to set email alerts
|

A Sport-Based Intervention to Increase Uptake of Voluntary Medical Male Circumcision Among Adolescent Male Students: Results From the MCUTS 2 Cluster-Randomized Trial in Bulawayo, Zimbabwe

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(69 citation statements)
references
References 12 publications
1
68
0
Order By: Relevance
“…Interventions were categorized into four major types: (i) financial incentives, (ii) counselling or education for prospective candidates, (iii) education and involvement of influencers, and (iv) novel information delivery, although some included more than one of these approaches. Most (n = 13) studies [13,[16][17][18][19][20][21]28,29,[31][32][33][34] presented data on the number of circumcisions completed at the end of the study period, while the remaining two studies [30,35] reported the prevalence of circumcision in the cohort. Table 2 shows the key findings from each study with both relative and absolute effects (where reported in the paper or calculated from raw data).…”
Section: Quantitative Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Interventions were categorized into four major types: (i) financial incentives, (ii) counselling or education for prospective candidates, (iii) education and involvement of influencers, and (iv) novel information delivery, although some included more than one of these approaches. Most (n = 13) studies [13,[16][17][18][19][20][21]28,29,[31][32][33][34] presented data on the number of circumcisions completed at the end of the study period, while the remaining two studies [30,35] reported the prevalence of circumcision in the cohort. Table 2 shows the key findings from each study with both relative and absolute effects (where reported in the paper or calculated from raw data).…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…Individual counselling is effective at increasing VMMC uptake when offered to men who had already taken the step of presenting to a VMMC facility . Group education or awareness raising interventions delivered in the community are also effective . Having time to process information between discussions allows for a natural decision‐making process; reviewing topics can reinforce benefits and alleviate new concerns .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In that study we find low overall demand for male circumcision: only 3 percent are circumcised over a three month period. Several other studies have found similar results (significant but small impacts) using a wide range of programs for examples using soccer programs to educate and motivate young men in Zimbabwe(Kaufman et al 2014), and conditional food vouchers were evaluated inKenya (Thirumurthy et al 2014).…”
mentioning
confidence: 79%